PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA ONLINE STORE GUZZLE DI MEDIA SOSIAL - Saputra, Naufal Hilmi; Thalib, Supriadi; Hendratni, Tyahya Whisnu (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to determine whether there is an influence of product quality and service quality on consumer satisfaction at Guzzle's online store on social media. The number of samples in this study was 100 respondents with nonprobability sampling and purposive sampling techniques. Data analysis techniques using hypothesis testing with the T-test (partial), F test (simultaneous) and the coefficient of determination test. Hypothesis test results with the T-test (partial) product quality has a positive effect on customer satisfaction and service quality has a positive effect on customer satisfaction. F test results (Simultaneous) concluded that product quality and service quality have a positive and significant effect on consumer satisfaction together. And the test results of the coefficient of determination of consumer satisfaction can be explained by the independent variables of product quality and service quality. Keywords: Product quality, Service quality, Customer satisfaction